Corporate finance : the basics - Tse, Terence C. M. (Abingdon, Oxon ; New York, NY : Routledge, 2018)
"Corporate Finance: The Basics is a concise introduction to the inner workings of finance at the company level. It aims to take the fear out of corporate finance and add the fun in, presenting the subject in a way that is simple to grasp and easy to digest. Its aim is to explain--and demystify--the essential ideas of corporate finance, avoiding the heavy use of calculations and formulae. The calculations and figures in the book are purely to illustrate fundamental concepts, appealing to readers' common sense, rather than stretch their ability to do "number-crunching". Topics covered include:Financial statements through the corporate finance lensHow to make investment decisionsCash versus profitNet working capital managementHow to determine the value of a businessThrough the use of a subject map, this book explains how the key components of the subject are connected with each other, strengthening the reader's understanding. This book is the ideal introduction for anyone looking for a short yet scholarly overview of corporate finance."--Provided by publisher.
chapter Introduction -- chapter 1 Financial statements -- chapter 2 Financial decisions and investment criteria -- chapter 3 Free cash? ows -- chapter 4 Net working capital management -- chapter 5 Debt -- chapter 6 Equity -- chapter 7 Mergers and acquisitions (I) -- chapter 8 Mergers and acquisitions (II) -- chapter 9 Corporate? nance: the big picture.
Keywords: Corporations -- Finance